A simple parametric formulation for the seabed trench profile beneath a steel catenary riser. (January 2016) - Wang, Kunpeng; Low, Ying Min
Abstract: Seabed trench has a profound influence on the fatigue performance of a steel catenary riser (SCR) at the touchdown zone. At present, the most well-regarded approach for simulating the complex trench development process is by applying a nonlinear hysteresis seabed contact model, which is time consuming. Field observations have indicated that the trench depth almost stabilizes after a few months following installation. Hence, for practical fatigue design, it is expedient to specify an initial static trench profile to perform the dynamic simulations. This paper presents a new simple parametric formulation for delineating an initial trench profile, as there appears to be no such approach in the literature. The formulation entails two unknown trench parameters (trench length and global trench position), which can be determined using a new iterative static analysis method proposed herein. However, the analysis involves solving a constrained optimization problem, and is not ideal for practical applications. Thus, a surrogate model is devised, by approximating the trench parameters as multivariate polynomial functions of three dimensionless variables of the SCR. A case study comparing the trenches obtained from seabed contact model, static analysis, and surrogate model, shows that the different trench profiles and the associated maximum fatigue damage are in close agreement. Highlights: Nonlinear seabed contact model can predict trench profile but very time consuming. New simple approach for modeling trench profile at touchdown zone of SCR. Trench and damage due to proposed approach agrees well with seabed contact model.